Effect of rice husk ash addition on the physical properties of soda-lime-silica glass for building glass and window - Alazemi, Mohammad F F S (2021)
One of the promising raw materials in producing glass is rice husk (RH), which contains about 90% of silica and is usually burnt in an open area which contributed to serious air pollution problems. The environmental issues of RH could be resolved by utilizing rice husk ash (RHA) as a silica source in the glass manufacturing process. The main objective of this research is to develop an ecofriendly Soda-Lime-Silica - Rice Husk Ash (SLS-RHA) glass for the application of building glass and window. Three main experiments were conducted; morphology test, ultrasonic velocities testing and Rockwell hardness test to assess the microstructure, elastic and mechanical behaviour of the developed SLS-RHA glass. Response surface methodology (RSM) was used to design the experiments incorporating two factors; such as the ratio of SLS to RHA and their interrelationship; and the effect on glass hardness properties were analysed using analysis of variance (ANOVA). From the morphology analysis, the addition of RHA to the glass former matrix increased the porosity of the glass which influenced the elastic properties of the newly developed glass. It was observed that sample two with 5% RHA wt. addition performed the finest under elastic properties test and the longitudinal and shear modulus of RHA glass decrease with the increased of RHA content. Sample with 5% of RHA possessed high and medium elastic properties, which make it easier to bend rather than elongate, less stiff, tough at a certain direction, and has low rigidity. The value of the longitudinal modulus decreased 7.12% with the addition of 10% RHA wt. Finally, for the hardness test, based on the observation from HRF, HRB and HRG contour plots which showed that the hardness values for each sample decreased as the RHA percentage increased in the SLS glass system. The hardness of the glass decreased with an increase in the addition of RHA content due to elastic deformation. The optimal solution obtained from ANOVA for the combination of RHA and SLS is SLS (A) 29.589% wt. and RHA (B) 0.031% wt. This formulation provided the results of 130.588 for HRF, 124.844 for HRB and 120.098 for HRG. It can be summarized that the use of silica from RHA efficiently improved the bulk modulus while maintaining a lower Young’s modulus value of the glass. This resulted in improved impact resistance of the glass due to a slower decelerated in smaller stress acting on the glass even though the glasses are less stiff. In this research, RHA proved to be a good silica source alternative for the glass manufacturing process, which can potentially improve the melting process temperature indirectly helps to reduce the cost of the manufacturing process.